EXPLORATION OF FINANCIAL MANAGEMENT PRACTICES IN TECHNOLOGY STARTUPS WITH A FOCUS ON CAPITAL AND RISK MANAGEMENT - Triana, Leni; Yuliah, Yuliah (Yayasan Education and Social Center, 2024)
This research aims to explore financial management practices in technology startups in Indonesia, with a focus on capital and risk management. Qualitative methods were used through in-depth interviews, observation and document analysis. The research results show that funding from venture capital is the main source for startups, which is used to support operations, product development and marketing. Working capital management is focused on cash flow efficiency to maintain financial stability amidst income fluctuations. Risk management is a significant challenge for startups, especially in the face of market volatility, intense competition and rapid technological change. Risk mitigation strategies include product diversification and assistance from venture capital. This research also found that the risk management systems in many Indonesian startups are still less integrated compared to companies in developed countries. These findings fill a gap in previous research and provide a perspective on financial management in developing country startup ecosystems. This research concludes that venture capital and effective risk mitigation strategies are key elements for the sustainability of technology startups. Further research is needed to understand the role of financial technology in startup financial management